(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The introduction of globalization has led to rising issues approximately the development of areas its miles envisaged that whilst the advanced areas will continue to grow similarly, the underdeveloped or backward regions would possibly similarly get marginalized. For maintaining average development, there is a need for a well-balanced improvement. For the motive, it is important to expand region-specific improvement strategies which can be framed on the idea of local context, which include assets. In India, with lifestyles of many backward regions, there is a want to identify the extent of backwardness and its volume so one can expand effective strategies for the improvement of the area. The present day observes examines the level and typology of improvement in Haryana district of Haryana. The Haryana location lies within the semi-arid area and is majorly inhabited through Meo Muslims. Water is scarce within the place, and therefore, rain is still the important supply of irrigation. Despite harsh climatic conditions, agriculture is the predominant livelihood option. Furthermore, because of cultural practices, farmers in Haryana use conventional farming techniques. In terms of several crucial socio-financial parameters, the Haryana district falls manner in the back of other elements of the us of a, in spite of being part of the prosperous state of Haryana.